A note on the typification of Hechtia galeottii (Hechtioideae, Bromeliaceae) - Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Martínez-Correa, Nancy; Till, Walter (Phytotaxa, 2013)
We explain why the lectotypification of Hechtia galeottii proposed by Smith & Downs is inaccurate and in serious conflict with the protologue and should be discarded. Accordingly, we propose a new lectotype and include a more detailed description of the species.